Sistem Informasi Penjualan Alat Dan Bahan Bangunan Di Toko Andalas Jaya Berbasis Web - Hsb, Zulpikar Hariansyah (Journal of Computer Science and Information System(JCoInS), 2021)
Abstract. At this time, there are a lot of several businesses such as sales of building materials play an important role in society, including in the case of sales made by some parts of the Company engaged in this building. Building retail companies generally sell tools and equipment building where one of them is for the sale of equipment and supplies fully equipped building and is provided by Andalas Jaya. In giving out the best service to customers / buyers / potential buyers urgently needed a computerized sales system and onlinebased. Where all the action today is very important for computerization and online-based. The purpose of research is done to make the Andalas Jaya is more efficient in the context of the sale of an easy to use web. The method used here is more directed to the research process by the Waterfall method. In the construction of such a system, in order to further facilitate the sales, transactions with ease, allowing the buyer to purchase goods online if distant, increase revenue and expand sales promotion at Anadalas Jaya.